The Implementation of Schleiermacher's Hermeneutics in The Interpretation of The Qur'an - Jufri Hasani Z; Sani, Azwar (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
This study aims to find out the use of hermeneutics in the interpretation of the Qur'an and consider how it can help in understanding and deepening the message contained in the Qur'an. This study used a qualitative approach with an evaluative analysis of Schleiermacher's work, 'Hermeneutics and Criticism.' This study offered a new contribution by systematically applying two main approaches, namely grammatical and psychological hermeneutics, in the context of the interpretation of the Qur'an. This research also integrated classical and contemporary interpretations to test the extent to which the power of hermeneutics could be used in understanding Islamic sacred texts. The results of the study showed that Schleiermacher's hermeneutic approach is able to make a significant contribution to broadening readers' understanding of the Qur'anic text comprehensively. Thus, the application of Schleiermacher's hermeneutics in the interpretation of the Qur'an has the potential to bridge the gap between the authority of the text and the modern experience of the reader, as well as open up opportunities for the development of an integrative and contextual interpretive framework. Therefore, this research is important as an exploratory effort in developing a deeper understanding of Islamic scriptures through the lens of philosophical hermeneutics.